2020
DOI: 10.1074/jbc.ra119.010438
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the DOCK-D family proteins in a mouse model of neuroinflammation

Abstract: The DOCK-D (dedicator of cytokinesis D) family proteins are atypical guanine nucleotide exchange factors that regulate Rho GTPase activity. The family consists of Zizimin1 (DOCK9), Zizimin2 (DOCK11), and Zizimin3 (DOCK10). Functions of the DOCK-D family proteins are presently not well-explored, and the role of the DOCK-D family in neuroinflammation is unknown. In this study, we generated three mouse lines in which DOCK9 (DOCK9−/−), DOCK10 (DOCK10−/−), or DOCK11 (DOCK11−/−) had been deleted and examined the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Similar to DOCK6, the DOCK-D subfamily member DOCK9 (also known as ZIZIMIN1) has been demonstrated to act as a GEF to both RAC1 and CDC42 [42,43,96]. In addition to strong associations with the nervous system, DOCK9 is implicated in vascular development and is expressed in HUVECs [16].…”
Section: Dock9mentioning
confidence: 99%
“…Similar to DOCK6, the DOCK-D subfamily member DOCK9 (also known as ZIZIMIN1) has been demonstrated to act as a GEF to both RAC1 and CDC42 [42,43,96]. In addition to strong associations with the nervous system, DOCK9 is implicated in vascular development and is expressed in HUVECs [16].…”
Section: Dock9mentioning
confidence: 99%
“…The DOCK-D subfamily, although not as well studied as other DOCKs, has been shown to have roles in the immune system and neurology ( 36 , 48 , 120 ). DOCK9 is a CDC42 GEF ( 35 ).…”
Section: Biological Function and Disease Associations Of The Dock Gefsmentioning
confidence: 99%
“…Such an interaction is worth investigation, as a reported point mutation in the AMPAR subunit GluA3 was shown to cause circadian rhythm disruption and intellectual disability ( 125 ). Knockout EAE mouse models of all DOCK-D family members were healthy and viable; DOCK9, however, had no reported change in phenotype, implying it is not involved in MS ( 120 ). Despite this result, the identification of structural remodeling as an important biological function of DOCK9 draws comparison to other family members, suggesting that further research is warranted in such areas as immune function.…”
Section: Biological Function and Disease Associations Of The Dock Gefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among DOCK-D family proteins (23)(24)(25), DOCK10 and DOCK11 are expressed by B cells (12,26). We and other groups previously reported that the lack of DOCK10 caused mild to no defects in the development of B cells or humoral immune responses (26)(27)(28)(29). Similarly, the lack of DOCK11 caused only mild, if any, defects in the development of B cells (28).…”
Section: Introductionmentioning
confidence: 96%